A model of student workload - Bowyer, Kyle (Routledge, 2012)
Student workload is a contributing factor to students deciding to withdraw from their study before completion of the course, at significant cost to students, institutions and society. The aim of this paper is to create a basic workload model for a group of undergraduate students studying business law units at Curtin University in Western Australia. In doing this, the paper explores the concept of undergraduate student workload by reviewing the literature on the subject, identifying factors that have an impact upon student workload, quantifying those factors, and creating a basic model of factors to be taken into account when assessing student workload.